Lithography Compatible, Flexible Micro‐Organic Light‐Emitting Diodes by Template‐Directed Growth. Issue 3 (23rd January 2019) - Zhu, Juan; Li, Jianping; Zhong, Qigang; Wang, Hong; Huang, Lizhen; Fontein, Florian; Hu, Laigui; Liu, Ran; Fuchs, Harald; Wang, Wenchong; Wang, Yandong; Chi, Lifeng
Abstract: In this work, high‐resolution flexible micro‐organic light‐emitting diodes (micro‐OLEDs) are presented by template‐directed growth. The templates are prepared by parallel patterning techniques (nanotransfer printing and photolithography) to create prepatterns on flexible substrates. The prepatterns act as nucleation sites and induce area‐selective growth of organic semiconductor molecules upon deposition. By optimization of growth parameters such as substrate temperature and growth rate, uniform patterns of diverse light‐emitting materials can be realized with feature sizes down to hundreds of nanometers, including orange, blue, and green emissions on the flexible substrates. Flexible micro‐OLEDs are further demonstrated based on the patterned organic semiconductors. By combination of parallel patterning techniques, this work provides a high yield and resolution patterning way for flexible organic electronics over large areas. Abstract : A high‐resolution patterning organic semiconductor with feature sizes down to hundreds of nanometers is realized on flexible substrates by template‐directed growth, which is compatible with parallel patterning techniques like soft lithography and photolithography. Various light‐emitting functional materials including orange, blue, and yellow‐green light can be created. The patterning of organic semiconductors is also demonstrated in the application of high‐resolution flexible OLED devices.